Geology and mineralization of the Daheishan supergiant porphyry molybdenum deposit (1.65 Bt), Jilin, China: A review - Nan Ju; Di Zhang; Guo-bin Zhang; Sen Zhang; Chuan-tao Ren; Yun-sheng Ren; Hui Wang; Yue Wu; Xin Liu; Lu Shi; Rong-rong Guo; Qun Yang; et al. (China Geology)
ABSTRACT: The Daheishan supergiant porphyry molybdenum deposit (also referred to as the Daheishan deposit) is the second largest molybdenum deposit in Asia and ranks fifth among the top seven molybdenum deposits globally with total molybdenum reserves of 1.65 billion tons, an average molybdenum ore grade of 0.081%, and molybdenum resources of 1.09 million tons. The main ore body is housed in the granodiorite porphyry plutons and their surrounding inequigranular granodiorite plutons, with high-grade ores largely located in the ore-bearing granodiorite porphyries in the middle-upper part of the porphyry plutons. Specifically, it appears as an ore pipe with a large upper part and a small lower part, measuring about 1700 m in length and width, extending for about 500 m vertically, and covering an area of 2.3 km2. Mineralogically, the main ore body consists of molybdenite, chalcopyrite, and sphalerite horizontally from its center outward and exhibits molybdenite, azurite, and pyrite vertically from top to bottom. The primary ore minerals include pyrite and molybdenite, and the secondary ore minerals include sphalerite, chalcopyrite, tetrahedrite, and scheelite, with average grades of molybdenum, copper, sulfur, gallium, and rhenium being 0.081%, 0.033%, 1.67%, 0.001%, and 0.0012%, respectively. The ore-forming fluids of the Daheishan deposit originated as the CO2-H2O-NaCl multiphase magmatic fluid system, rich in CO2 and bearing minor amounts of CH4, N2, and H2S, and later mixed with meteoric precipitation. In various mineralization stages, the ore-forming fluids had homogenization temperatures of > 420°C–400°C, 360°C–350°C, 340°C–230°C, 220°C–210°C, and 180°C–160°C and salinities of > 41.05%–9.8% NaCleqv, 38.16%–4.48% NaCleqv, 35.78%–4.49% NaCleqv, 7.43% NaCleqv, and 7.8%–9.5% NaCleqv, respectively. The mineralization of the Daheishan deposit occurred at 186–167 Ma. The granites closely related to the mineralization include granodiorites (granodiorite porphyries) and monzogranites (monzogranite porphyries), which were mineralized after magmatic evolution (189–167 Ma). Moreover, these mineralization-related granites exhibit low initial strontium content and high initial neodymium content, indicating that these granites underwent crust-mantle mixing. The Daheishan deposit formed during the Early-Middle Jurassic, during which basaltic magma underplating induced the lower-crust melting, leading to the formation of magma chambers. After the fractional crystallization of magmas, ore-bearing fluids formed. As the temperature and pressure decreased, the ore-bearing fluids boiled drops while ascending, leading to massive unloading of metal elements. Consequently, brecciated and veinlet-disseminated ore bodies formed.©2023 China Geology Editorial Office.